Ion-beam sources based on superionic solid electrolytes - Fernandes, Fábio Joel Pereira (2016)
An ion emitter consisting of a sharp silver tip covered in RbAg4I5 solid electrolyte film has been developed and studied. An accelerating potential is applied and Ag+ ions are emitted from the tip’s apex by field evaporation. The emitted ions are collected by a Faraday cup, producing a current on the pico/nanoampere level which is read by an electrometer. The tips were produced mechanically by sandpaper polishing. The sharpest tip produced had a 2:4 m apex radius. Two deposition methods were studied: thermal vacuum and pulsed laser deposition. The best tip produced a peak current value of 96nA at 180oC, and a quasi-stable 4nA emission current at 160oC, both using an extraction potential of 10kV . The emission dependence on time, temperature and accelerating potential has been studied. Deposited films were characterized by X-ray diffraction (XRD), profilometry, optical and Scanning Electron Microscope (SEM) and Secondary Ion Mass Spectroscopy (SIMS) measurements. Several ion emitters were developed, the latter ones were all able to maintain stable high ion emissions for long periods of time. This investigation was a continuation of an ongoing project backed by the European Space Agency, with the objective of making a proof of concept of this kind of ion emitter with potential application on ion thrusters for orbiting satellites. Going forward, it would be interesting to make a finer analysis of the electrolyte’s conductivity at high temperatures, explore Wien Effect-based emission and to further develop a multi-tip ion emitter prototype.